2004
DOI: 10.1177/153303460400300207
|View full text |Cite
|
Sign up to set email alerts
|

Cryosurgery for Lung Cancer: Clinical Results and Technical Aspects

Abstract: Lung carcinoma is the most frequently diagnosed malignancy in the world, with the incidence increasing through the 20 th century. Presentation may be as a tumor mass primarily obstructing the central bronchial lumen, or a mass infiltrating lung tissue. Cryosurgery can be used as a method of palliative treatment for both these endobronchial and extrabronchial presentations. The aim of this study is two-fold: to present data relating to our extensive experience in treating obstructing endobronchial tumors and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
66
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 14 publications
4
66
0
2
Order By: Relevance
“…They inserted cryoprobes although the lung was ventilated and performed the therapy. By 6 months 86% of the treated areas were stable or smaller than the original tumor [10]. Pneumothorax due to the procedure occurred in 12% of the patients and only a few of them required tube thoracostomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They inserted cryoprobes although the lung was ventilated and performed the therapy. By 6 months 86% of the treated areas were stable or smaller than the original tumor [10]. Pneumothorax due to the procedure occurred in 12% of the patients and only a few of them required tube thoracostomy.…”
Section: Discussionmentioning
confidence: 99%
“…It is a treatment option for patients with an airway obstruction, alternative to laser, diathermia, photodynamic therapy and stent applications [10][11][12][13][14][15][16]. Cryotherapy with minimal complication ratios were reported to be a good tolerated method by Maiwant et al [17][18].…”
Section: Discussionmentioning
confidence: 99%
“…With cryo-recanalisation, a normal bronchial calibre can be recovered in 61-91% of cases [34,43,44], allowing for the removal of 57% and 76% of total and lobar atelectasis, respectively [32]. A 54.6% improvement in the Karnofsky performance status index is due to a significant functional benefit, with an improvement in FEV1 and FVC of 65.2% and 57.8%, respectively [42], and of partial pressure of oxygen (71% of cases) [32].…”
Section: Cryotherapymentioning
confidence: 99%
“…This process requires a console, a cryoprobe [34,35] and cryogenic gas (N 2 O, N 2 , CO 2 [9,34]). The destructive damage inflicted by cryotherapy is both immediate (dehydration and cellular crystallisation) [7,[36][37][38][39] and delayed, involving apoptosis and ischaemia (microthrombi formation) [40], leading to a delayed yet prolonged result [7,36].…”
Section: Cryotherapymentioning
confidence: 99%
“…Biopsy via cryoprobe, rst used in 1968, has mainly been employed in the management of obstructive endobronchial tumors. Recently, cryotherapy in bronchoscopy has been used for several purposes including management of endobronchial tuberculosis [10], endobronchial tumors [11][12][13], for diagnosis of interstitial lung disease (ILD) [14][15][16][17], and peripheral lung lesion [18]. ese studies have demonstrated that the cryoprobe is feasible and a more e cient diagnostic tool with a superior diagnostic rate and ability to obtain a larger specimen with better preserved cellular architecture than forceps biopsy.…”
Section: Introductionmentioning
confidence: 99%